New Area Studies as an Epistemological Framework: Some Reflections of Knowledge Production and Positionality - Marianela Barrios Aquino (New Area Studies)
New Area Studies can be seen as resulting from the debate in the Area Studies between the need for disciplinarity and the urgency of ethical research practices in the social sciences. As such, it is fertile ground for reflexions on methodology, knowledge production and the construction of epistemic communities that go beyond disciplinary silos. In this paper, I argue that New Area Studies is useful as a lens through which to engage with decolonial and postcolonial critiques of the social sciences and humanities. To present New Area Studies as an epistemological framework, in this theoretical intervention, I first engage with its origins in the field of Area Studies and the critiques aimed at it. Next, I propose that taking such critique seriously involves necessarily a discussion of knowledge production and research practice. Finally, I propose that New Area Studies can be understood as an epistemological framework useful to address contemporary challenges faced by all social sciences, not only Area Studies. This paper weaves together decolonial and feminist approaches to research, to argue for the relevance of New Area Studies scholarship.